Characterization of a sCMOS‐based high‐resolution imaging system. (13th October 2017) - Mittone, Alberto; Manakov, Ilja; Broche, Ludovic; Jarnias, Christophe; Coan, Paola; Bravin, Alberto
Abstract : The detection system is a key part of any imaging station. Here the performance of the novel sCMOS‐based detection system installed at the ID17 biomedical beamline of the European Synchrotron Radiation Facility and dedicated to high‐resolution computed‐tomography imaging is analysed. Abstract : The detection system is a key part of any imaging station. Here the performance of the novel sCMOS‐based detection system installed at the ID17 biomedical beamline of the European Synchrotron Radiation Facility and dedicated to high‐resolution computed‐tomography imaging is analysed. The system consists of an X‐ray–visible‐light converter, a visible‐light optics and a PCO.Edge5.5 sCMOS detector. Measurements of the optical characteristics, the linearity of the system, the detection lag, the modulation transfer function, the normalized power spectrum, the detective quantum efficiency and the photon transfer curve are presented and discussed. The study was carried out at two different X‐ray energies (35 and 50 keV) using both 2× and 1× optical magnification systems. The final pixel size resulted in 3.1 and 6.2 µm, respectively. The measured characteristic parameters of the PCO.Edge5.5 are in good agreement with the manufacturer specifications. Fast imaging can be achieved using this detection system, but at the price of unavoidable losses in terms of image quality. The way in which the X‐ray beam inhomogeneity limited some of the performances of the system is also discussed.